The Effect of Kirinyuh Leaf (Euphatorium odoratum) Solvent with Different Doses on Hatching Rate of Tambaqui Larvae (Colossoma macropomum) - Nugraha, Aditya; Sukendi, Sukendi; Aryani, Netti (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
This research was conducted on April - May 2021, at Fish Hatchery and Breeding Laboratory of Fishery and Marine Science Faculty of Riau University. The aim of this research was to determine the effect of Kirinyuh leaf (Euphatorium odoratum) solvent and the optimal dose on hatching rate of tambaqui larvae (Colossoma macropomum). The method used was a Completely Randomized Design Factorial with 4 treatments and 3 replications. The dose of kirinyuh leaf solvent used was P0 (0 mg/L) P1 (100 mg/L) P2 (120 mg/L) and P3 (140 mg/L). rGH with 3 levels; 0 mg/L (D0), 1.5 mg/L (D1,5) and 2.5 mg/L (D2,5). The immersion duration of kirinyuh leaf solvent is 20 minutes with 100 eggs for the density. The results showed that the use of different doses of kirinyuh leaf solvent gave very real effect to fertilization rate with highiest point (87,33%) following with hatching rate (88,00%), and survival rate (83,66%).